2018
DOI: 10.4314/jfas.v9i6s.74
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics analysis of step and jump forward lunge among badminton players

Abstract: This study was conducted to determine and compare the kinetics during step forward lunge (SFL) and jump forward lunge (JFL) in badminton. Fifteen university badminton players (mean age = 22.07 ± 1.39 years old) were recruited and were assigned to perform SFL and JFL while holding a badminton racquet using their dominant hand. For both dominant and non-dominant leg, all the force variables during JFL were significantly higher compared to SFL. Results also showed that time to peak force and stance time was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Currently, lack of study has been conducted on the fascicle behaviour during resistance training. The fascicle behaviour during lunge movement was the current study interest as this movement was one of the most specific movement in many sports [22][23][24][25]. Results in this study showed that FLmax, FLmin, PAmax and PAmin were all greater during 70FL compared to 30FL, p < 0.001.…”
Section: Discussionmentioning
confidence: 67%
“…Currently, lack of study has been conducted on the fascicle behaviour during resistance training. The fascicle behaviour during lunge movement was the current study interest as this movement was one of the most specific movement in many sports [22][23][24][25]. Results in this study showed that FLmax, FLmin, PAmax and PAmin were all greater during 70FL compared to 30FL, p < 0.001.…”
Section: Discussionmentioning
confidence: 67%
“…This means that, if 100 times the shuttlecock were sent to the front, the right leg will have to perform 100 times of lunge. This demonstrates the possibility of asymmetry exists (16,18,19) among the players even the players that we analysed are in a very high level. The numbers of lunge perform laterally and to the back are also quite high.…”
Section: Discussionmentioning
confidence: 88%
“…Coaches and players need to take note on this especially those that did not implement lunge as one of their training exercise. 264 lunge movements are very high, as each of the lunges will exert force almost similar to their bodyweight (16,17). By including lunge as one of the training exercise would benefit the players in terms of how to perform the movement in correct way, as wrong technique will always imposed the players to risks of injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The other ways to catch up with the shuttlecock is by lunge. If the players can perform good lunge, they will be able to cover the court easier (13)(14)(15). Without good agility, players definitely will not be able to prepare and could cause them to lose the match.…”
Section: Discussionmentioning
confidence: 99%